PARTISIPASI MASYARAKAT DESA DALAM PENGELOLAAN DESA WISATA (STUDI KASUS PADA DESA WISATA PANDEAN, KECAMATAN DONGKO, KABUPATEN TRENGGALEK) - Puspitasari, Yeni; Eprilianto, Deby Febriyan (Publika, 2023)
Village economic development can be increased through the capacity and skills of the community in managing existing tourism potential, one of which is through tourist villages. Pandean Tourism Village as a new tourist village object has achieved extraordinary achievements. However, behind its success, the community is less involved in its management and the income from tourism village activities has not made a special contribution to the village's original income. Therefore the purpose of this study is to describe and explain the participation of village communities in the management of Pandean Tourism Village. The method used in this study is descriptive with a qualitative approach. The data collection techniques through observation, interviews and documentation were then analyzed using an interactive data analysis model according to Miles and Huberman. While the research focus used is the theory of participation according to Cohen and Uphoff in Nurbaiti (2017) which includes a) the decision-making stage, b) the implementation stage, c) the results utilization stage, and d) the evaluation stage. The results of the study show that community participation in decision making is still low, but the community participates quite well in evaluation activities. The existence of this Pandean tourism village has benefited the village, administrators, district and especially the community. The community also actively participates in implementation activities, especially in providing material and labor contributions. In managing the Pandean Tourism Village, researchers suggest conducting outreach activities or informal activities to the community so that they are willing and brave to provide ideas, opinions and suggestions, establish distribution houses for MSME actors, the community is often involved in tourism village management activities and increase public awareness to care on environmental cleanliness. Keywords: Participation, Community, Tourism Village